Evaluation of insulating panels made of cattails fibers (Typha Latifolia) (Gaceta Técnica, 2016)
In this paper the insulating capacity of panels made of Typha latifolia in different forms was evaluated. The results show a significant insulating capacity, placing the cattail as a potential isolating element in buildings. The development of thermal insulation elements based on biomass residues is a promising line of research that will provide substantial improvement in energy efficiency and thermal comfort with sustainable habitat solutions at low cost. The development of contemporary construction elements such as panels or blankets of totora, will permit the improvement of industrial solutions sustainability and a significant reduction in the cost of its production
Keywords: insulating capacity; Typha latifolia; thermic panels